The Influence of Temporal Specification on the Identification of Crime Hot Spots for Program Evaluations: A Test of Longitudinal Stability in Crime Patterns - Schnell, Cory (Journal of quantitative criminology, 2022)
Objectives Longitudinal studies from the criminology of place suggest crime hot spots are repeatedly found in the same locations within cities over extended periods of time. Program evaluations of hot spots policing interventions often use much shorter temporal windows to define hot spots. This study examines if stability of patterns is still found when using short and intermediate periods of time to measure crime hot spots. Methods We examined 765,235 total crime incidents reported to the Cincinnati Police Department from 1997 to 2016. These incidents were geocoded to 13,189 street segments. We created measures of crime hot spots based on varying temporal periods using three different strategies: pooled observations, group-based trajectory modeling, and k-means clustering. These measures were compared using techniques associated with survival analyses to determine the influence of temporal specification on the retrospective identification of crime hot spots. Results Our findings suggest regardless of the temporal specification, most street segments identified as crime hot spots remained crime hot spots across the observed follow-up periods. There was still much variability in patterns based upon temporal specifications and the use of additional years of incident report data did not uniformly provide an improved understanding of which street segments remained crime hot spots. Conclusions Program evaluations of hot spots policing strategies do not need to use extended periods of time to observe stability in crime hot spots. The criminology of place should provide more attention to the topic of temporal specification and continue exploring the utility of crime hot spots.